The island where climate change is not the biggest worry: Hatiya Island, Bangladesh - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
This carousel challenges common assumptions about climate vulnerability through the example of Hatiya Island in Bangladesh. Despite frequent flooding, cyclones, and crop losses, local residents identified debt, rising food prices, and failing health and education systems as their greatest concerns. The story shows that climate shocks rarely act alone and that underlying economic and social pressures shape how communities experience risk. By highlighting these intersecting stresses, the carousel reframes resilience as more than surviving disasters, calling for responses that address structural vulnerabilities alongside climate impacts.